1991
DOI: 10.1159/000261340
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of Bovine Incisor Root Lesions in vitro: The Role of the Collagenous Matrix

Abstract: This study deals with the role of collagen in the remineralization of bovine incisor root lesions. The degradability of the collagenous matrix after in vitro remineralization was also investigated. The root surfaces were exposed to 0.1 M acetic acid, pH 4.0, to produce erosive lesions or to 0.1 M lactic acid, 0.2 mM methane hydroxy diphosphonate, pH 5.0, to produce subsurface lesions. After demineralization, the roots were subjected to remineralization, with or without prior treatment with a bacterial collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
12

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 18 publications
6
73
1
12
Order By: Relevance
“…With this barrier, the acid diffusing inward and the dentin mineral diffusing outward were retarded, thereby inhibiting further demineralization of Ca and phosphate ions from the lesion body 15) . However, Klont revealed that there was no influence on lesion remineralization in-vitro when removing demineralized collagen by enzyme 16) . Present authors hypothesized that inhibiting collagen degradation leads to anti-demineralization in dentin.…”
Section: Introductionmentioning
confidence: 99%
“…With this barrier, the acid diffusing inward and the dentin mineral diffusing outward were retarded, thereby inhibiting further demineralization of Ca and phosphate ions from the lesion body 15) . However, Klont revealed that there was no influence on lesion remineralization in-vitro when removing demineralized collagen by enzyme 16) . Present authors hypothesized that inhibiting collagen degradation leads to anti-demineralization in dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Because high concentration of fluorine was detected into hybrid layer, we guessed deposits of fluoroapatite in the collagen network of the hybrid layer; this remineralization of dentin occurs by precipitation onto residual crystals [25]. Thus, the hybrid layer might be reinforced by the remineralization process.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the functions mentioned above, fluoride ions penetrating into the dentin have been shown to enhance mineralization of the dentin [61][62][63]. This applies especially to the improved dissolution resistance initiated by epitaxial deposition of fluorapatite over remnant apatite crystallites in the hybrid layer [64]. In this conventional remineralization strategy, fluoride requires the presence of some apatite crystals in the partially demineralized dentin to initiate deposition of new mineral [65].…”
Section: Fluoride-containing Adhesivesmentioning
confidence: 99%